2020
DOI: 10.1177/1369433220945055
|View full text |Cite
|
Sign up to set email alerts
|

Strength reduction factor of self-centering structures under near-fault pulse-like ground motions

Abstract: Many studies on the strength reduction factor mainly focused on structures with the conventional hysteretic models. However, for the self-centering structure with the typical flag-shaped hysteretic behavior, the corresponding study is limited. The main purpose of this study is to investigate the strength reduction factor of the self-centering structure with flag-shaped hysteretic behavior subjected to near-fault pulse-like ground motions by the time history analysis. For this purpose, the smooth flag-shaped mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The proposed dynamic theoretical model can evaluate the seismic performance of the SC pier system more easily, accurately, and comprehensively. In addition, some studies 37,38 have indicated that, under near-fault earthquake ground motions, much larger seismic responses of SC systems would occur because of high-energy pulse action. This could significantly amplify the impact effect on the rocking interface.…”
Section: Influence Of the Impact Force On The Rocking Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The proposed dynamic theoretical model can evaluate the seismic performance of the SC pier system more easily, accurately, and comprehensively. In addition, some studies 37,38 have indicated that, under near-fault earthquake ground motions, much larger seismic responses of SC systems would occur because of high-energy pulse action. This could significantly amplify the impact effect on the rocking interface.…”
Section: Influence Of the Impact Force On The Rocking Interfacementioning
confidence: 99%
“…In addition, some studies 37,38 have indicated that, under near‐fault earthquake ground motions, much larger seismic responses of SC systems would occur because of high‐energy pulse action. This could significantly amplify the impact effect on the rocking interface.…”
Section: Influence Of the Impact Effect On The Seismic Responsementioning
confidence: 99%